Aquaporin 1a Expression in Gill, Intestine, and Kidney of the Euryhaline Silver Sea Bream - Deane, Eddie E.; Luk, James C.; Woo, Norman Y. S. (Frontiers in Physiology, 2011)
This study aimed to investigate the effects of chronic salinity acclimation, abrupt salinity transfer and cortisol administration on aquaporin 1 (AQP1) expression in gill, intestine and kidney of silver sea bream (Sparus sarba). An AQP1a cDNA was cloned and found to share 83 – 96 % amino acid sequence identity with AQP1 genes from several fish species. Tissue distribution studies of AQP1a mRNA demonstrated that it was expressed in gill, liver, intestine, rectum, kidney, heart, urinary bladder and whole blood. Semi-quantitative RT-PCR analysis was used to measure AQP1a transcript abundance in sea bream that were acclimated to salinity conditions of 0, 6, 12, 33, 50 and 70ppt for 1 month. The abundance of gill AQP1a transcript was highest in sea bream acclimated to 0ppt whereas no differences were found among 0 – 50ppt groups. For intestine, the highest AQP1a transcript amounts were found in sea bream acclimated to 12 and 70ppt whereas the transcript abundance of kidney AQP1a was found to be unchanged amongst the different salinity groups. To investigate the effects of acute salinity alterations on AQP1a expression, sea bream were abruptly transferred from 33ppt to 6ppt. For intestine AQP1a levels were altered at different times, post transfer, but remained unchanged in gill and kidney. To study the effects of cortisol on AQP1a expression, sea bream were administered a single dose of cortisol followed by a 3 day acclimation to either 33ppt or 6ppt. The findings from this experiment demonstrated that cortisol administration resulted in alterations of AQP1a transcript in gill and intestine but not in kidney.